2017
DOI: 10.1080/02640414.2017.1332420
|View full text |Cite|
|
Sign up to set email alerts
|

New evidence of relative age effects in “super-elite” sportsmen: a case for the survival and evolution of the fittest

Abstract: The relative age effect (RAE) describes an overrepresentation of players born early (Q1) in a selection year and is highly prevalent within youth sport pathways. However, a dearth of research has investigated the RAE at the "super-elite" level. The present research assessed the presence of RAE in super-elite performers. Study 1 investigated RAEs in the world's best international Test cricketers (N = 262) over a 20-year period according to a robust and stringent "super-elite" criteria. Results revealed the RAE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 14 publications
3
39
1
4
Order By: Relevance
“…These results, in men's sport, are in line with other studies that confirmed that relatively young players, considered as "talented, " achieved more and greater attainments throughout their sport career in terms of competitive experience (Carling et al, 2009), competitive productivity (Sims and Addona, 2016), longevity of sport career (Jones et al, 2018), ranking position (Ford and Williams, 2011), or salary (Ashworth and Heyndels, 2007). These results, given the relevance of team sports in their respective sociocultural contexts, could be explained by the "underdog effect" (Gibbs et al, 2012).…”
Section: Rae and Competition Performance By Gendersupporting
confidence: 90%
See 1 more Smart Citation
“…These results, in men's sport, are in line with other studies that confirmed that relatively young players, considered as "talented, " achieved more and greater attainments throughout their sport career in terms of competitive experience (Carling et al, 2009), competitive productivity (Sims and Addona, 2016), longevity of sport career (Jones et al, 2018), ranking position (Ford and Williams, 2011), or salary (Ashworth and Heyndels, 2007). These results, given the relevance of team sports in their respective sociocultural contexts, could be explained by the "underdog effect" (Gibbs et al, 2012).…”
Section: Rae and Competition Performance By Gendersupporting
confidence: 90%
“…In this kind of studies, the impact and magnitude of the RAE can be accurately evaluated, but they have the inconvenience of assuming an equal distribution of the athletes by grouping method throughout the year (Dixon et al, 2020 ). On the other hand, studies based on the “longitudinal performance analysis” have proliferated with the aim of verifying the consequences derived from the RAE throughout the sport careers (Steingröver et al, 2016 ; Fumarco et al, 2017 ; Jones et al, 2018 ). The indicators most used to assess long-term performance have been individual or collective cumulative statistics, position in the ranking, victory rates, or number of national/international appearances.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of an RAE has been observed at the senior and youth levels in the following contact team sports: basketball (Arrieta et al, 2016;Werneck et al, 2016), soccer (González-Víllora et al, 2015;Skorski et al, 2016), and handball (Schorer et al, 2009). Contrary, the RAE was not found in other team sports such as rugby (Jones et al, 2018) and water polo (Barrenetxea-Garcia et al, 2018). In line with this, the findings of existing literature on RAE in contact team sports have been controversial so far.…”
Section: Introductionmentioning
confidence: 98%
“…These factors have been studied with different approaches, focusing on athlete talent development career transitions [18,[23][24][25] or talent development as a holistic phenomenon [13,14,16,26,27]. In both cases, a vital itinerary has been a recurrent tool to study in depth elite career pathways [8,23,[28][29][30][31][32][33][34], since it allows the investigators to understand the factors affecting the athlete and his circumstances. Stambulova et al [24] already talked about the importance of such circumstances, especially when considering their cultural framework.…”
Section: Introductionmentioning
confidence: 99%